Comparison of conditioning regimen toxicities among autologous stem cell transplantation eligible multiple myeloma patients: High-dose melphalan versus high-dose melphalan and bortezomib - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2018)
Background Autologous hematopoietic stem cell transplantation (AHSCT) remains the standard of care for younger patients with multiple myeloma (MM). Currently, high-dose melphalan (HDM) is recommended as conditioning regimen before AHSCT. Preclinical data suggest that combining bortezomib and melphalan has synergistic effect against multiple myeloma cells. Bortezomib and HDM (Bor-HDM) combination as conditioning regimen has been investigated by many other investigators. Objective In this retrospective study, we aimed to compare transplant-related toxicities and hematologic recovery of HDM and Bor-HDM conditioning regimens. Method We retrospectively evaluated hematologic recovery and toxicity profile in patients with MM who received AHSCT with either HDM (n=114) or Bor-HDM (n=53) conditioning regimen. Results Nonhematologic toxicities were comparable between HDM and Bor-HDM conditioning regimen, except mucositis and diarrhea being more frequent in the Bor-HDM group. Neutrophil and platelet engraftment time and duration of hospital stay were significantly shorter for HDM regimen. Conclusions In this retrospective analysis, we observed engraftment kinetics and duration of hospitalization were significantly worse in Bor-HDM conditioning regimen with manageable toxicities. Randomized studies are needed to further compare Bor- HDM regimen to HDM in terms of response rates, toxicities, and transplant-related mortality.
Keywords: Multiple myeloma; bortezomib; autologous stem cell transplantation; conditioning regimen; melphalan; PHASE I/II TRIAL; RANDOMIZED-TRIAL; INTERGROUPE FRANCOPHONE; CHEMOTHERAPEUTIC-AGENTS; ARSENIC TRIOXIDE; ASCORBIC-ACID; EARLY RELAPSE; 200 MG/M(2); AUTO-SCT; SURVIVAL